Process optimization for the preparation of Burfi applying ISSHE with CPV and Mechanized cooling system - Vekariya, YogeshKumar; Hati, Subrota; Kathiriya, Mital; Sawhney, IK (Indian Journal of Dairy Science, 2014)
Integrated Scraped Surface Heat Exchanger (ISSHE) with Conical Process Vat (CPV) andÂ Â  Mechanized Cooling System (MCS) were used for in-line process optimization of Burfi. Central composite rotatable design (CCRD) was used to conduct experiments. Optimization was carried out using response surface methodology (RSM) based on its textural and sensory attributes. The three factors i.e. CPV steam pressure (1.0-1.5 kg/cm2,g), stage of sugar addition (45-50%TS concentration of milk) and rotor speed of continuous cooling system (6-9 rpm) were considered for in-line production of Burfi . Optimized parameters for Burfi production were evaluated as 1.5 kg/cm2 steam pressure (after sugar addition), 50%TS concentration of milk (stage of sugar addition) and 8 rpm rotor speed of mechanized cooling system. The optimized values for hardness, gumminess, chewiness and average sensory score viz. flavour, body & texture and colour & appearance were 3.86, 0.54, 0.108, 37.76, 29.09 and 12.27 respectively.